Detecting early-stage breast cancer with GATA3-positive circulating tumor cells - Chun-Hsin Hsieh; Ya-Herng Chang; Pei-Ying Ling; Ying-Tai Jin; Pei-Hsuan Lo; Hei-Jen Jou (Elsevier, 2024)
Objective: This case demonstrated the possibility of using GATA3-positive circulating tumor cells (CTCs) to detect early-stage breast cancer (BrC). Case report: The 86 years old female patient received a mammographic examination with no evidence of malignancy (Breast Imaging Reporting and Data System, (BI-RADS category 2). However, CTC testing on the same day revealed four GATA3-positive CTCs in 4 ml of peripheral blood. Core needle biopsy was performed in the suspicious area even with no evidence of malignant image on breast ultrasound. Pathologic examination showed invasive carcinoma of no special type of the breast. The patient then received an oncoplastic partial mastectomy of right breast and sentinel lymph node biopsy. The surgical staging was cT1N0M0. Post-operation follow-up examination showed absence of GATA3-positive CTCs and the presence of HER2/ER positive CTCs. Conclusion: The role of GATA3-positive CTCs as a potential biomarker for early-stage BrC should be explored.